Investigation of heat transfer characteristics when burning the coal-dust torch n the combustion chamberof the boiler BKZ-160 - Аскарова, А.С.; Болегенова, С.А.; Болегенова, Сымбат; Максимов, В.Ю.; Ергалиева, А.Б.; Габитова, З.Х.; Боранбаева, А.Е. (Recent Contributions to Physics, 2016)
Researches of various chemical processes in the gas environment are relevant today, as discussed in many areas of science and technology, and are of great practical interest for researchers and engineers. The aim of this study was to conduct a computational experiment to determine the basic characteristics of the heat exchange in the combustion chamber of the real energy facility-BKZ-160 of the AlmatyCHP-3. The methodology of work is- the method of mathematical modeling which was conducted with the help of the application package FLOREAN. The results of study was to investigate the processes of heat exchange, which will allow us in this study to determine the distribution of temperature, chemical energy, and the oxygen concentration in the entire volume of the combustion chamber.